Conservation and immunogenicity of novel antigens in diverse isolates of enterotoxigenic Escherichia coli. - Qingwei Luo; Firdausi Qadri; Rita Kansal; David A Rasko; Alaullah Sheikh; James M Fleckenstein (PLOS Neglected Tropical Diseases, 2015)
Background Enterotoxigenic Escherichia coli (ETEC) are common causes of diarrheal morbidity and mortality in developing countries for which there is currently no vaccine. Heterogeneity in classical ETEC antigens known as colonization factors (CFs) and poor efficacy of toxoid-based approaches to date have impeded development of a broadly protective ETEC vaccine, prompting searches for novel molecular targets. Methodology Using a variety of molecular methods, we examined a large collection of ETEC isolates for production of two secreted plasmid-encoded pathotype-specific antigens, the EtpA extracellular adhesin, and EatA, a mucin-degrading serine protease; and two chromosomally-encoded molecules, the YghJ metalloprotease and the EaeH adhesin, that are not specific to the ETEC pathovar, but which have been implicated in ETEC pathogenesis. ELISA assays were also performed on control and convalescent sera to characterize the immune response to these antigens. Finally, mice were immunized with recombinant EtpA (rEtpA), and a protease deficient version of the secreted EatA passenger domain (rEatApH134R) to examine the feasibility of combining these molecules in a subunit vaccine approach. Principal findings EtpA and EatA were secreted by more than half of all ETEC, distributed over diverse phylogenetic lineages belonging to multiple CF groups, and exhibited surprisingly little sequence variation. Both chromosomally-encoded molecules were also identified in a wide variety of ETEC strains and YghJ was secreted by 89% of isolates. Antibodies against both the ETEC pathovar-specific and conserved E. coli antigens were present in significantly higher titers in convalescent samples from subjects with ETEC infection than controls suggesting that each of these antigens is produced and recognized during infection. Finally, co-immunization of mice with rEtpA and rEatApH134R offered significant protection against ETEC infection. Conclusions Collectively, these data suggest that novel antigens could significantly complement current ...